Prevalence and maternal-fetal outcomes of obstetric cholestasis in a tertiary care teaching hospital - Shrestha, Sarada Duwal; Timalsina, Gyanu; Maharjan, Anjali (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Obstetric cholestasis (OC) is a pregnancy-specific liver disorder associated with pruritus and elevated bile acids, leading to increased risks of preterm delivery, fetal distress, and stillbirth. This study aimed to determine the prevalence and maternal and fetal outcomes of obstetric cholestasis in a tertiary care teaching hospital.Method: This retrospective study included all women diagnosed with obstetric cholestasis at the Department of Obstetrics and Gynaecology, Patan Hospital, Patan Academy of Health Sciences, Lalitpur, Nepal, from April 2022 to March 2025. Demographic, obstetric, maternal, and fetal outcome data were retrieved from hospital records for analysis.Result: Among 16,628 deliveries, 166 women were diagnosed with obstetric cholestasis, yielding a prevalence of 1.0%. Most affected women were aged 20–34 years (82.5%) and primigravida (52.4%). Diagnosis was most common at 34–37 weeks of gestation (43.4%), and 75.3% delivered at term. Maternal comorbidities included diabetes (28.3%), hypothyroidism (19.9%), and hypertension (4.2%). Cesarean section was the predominant mode of delivery (68.7%), with 53.0% performed as emergency procedures; labour induction was carried out in 53.0% of cases. Preterm delivery occurred in 23.5%. Adverse fetal outcomes included low birth weight (30.1%), prematurity (23.5%), intrauterine growth restriction (18.7%), and fetal distress (16.9%), with no stillbirths reported.Conclusion: Obstetric cholestasis affected 1% of women, mainly primigravida aged 20–34 years, and was associated with higher rates of cesarean delivery, labour induction, preterm birth, and adverse fetal outcomes, including low birth weight, prematurity, intrauterine growth restriction, and fetal distress, without any stillbirths.